التمويل المصرفي الإسلامي للمشروعات الصغيرة الصومال دراسة استكشافية - Yasin 'Abd 'Alsu
This study highlights the role of Islamic banking finance for small enterprises in Somalia aiming to identify the reality of Islamic banking financing for small enterprises, and to explain its relationship with social and economic development and their effects on Somali society. The researcher addressed the problem study which arise due to the absence of supporting parties for small projects. Thus, the financing dilemma is one of the recurring problems facing small enterprises in Somalia and leads to their cessation. The study derives its importance from the fact that it deals with the role of Islamic banks in the development of small enterprises. These are considered as one of the most important means of social and economic development in Somalia. The researcher sought to answer the following research questions: What are small projects? What are the limits of Islamic banking financing for small projects? How to apply Islamic banking financing contracts for small projects in Somalia? To complete this study, the researcher followed the descriptive, analytical, and inductive approach. Furthermore, the researcher also used the field study approach through the personal interviews conducted by the researcher. The questions were directed to the founders of financing projects and workers in the entities, the official in charge directly related to the field of Islamic banking and those responsible for financing small projects in Somalia. This study concluded several important results, including: There are methods of financing based on contributions and charity, and other methods based on Islamic financing contracts, as well as investor financing for projects based on permissible benefits for the Somali community. The study recommended the necessity of activating Islamic financing contracts for small projects without focusing on a single method only.